2016
DOI: 10.1148/radiol.2015150577
|View full text |Cite
|
Sign up to set email alerts
|

CT Image Contrast of High-ZElements: Phantom Imaging Studies and Clinical Implications

Abstract: Purpose:To quantify the computed tomographic (CT) image contrast produced by potentially useful contrast material elements in clinically relevant imaging conditions. Materials and Methods:Equal mass concentrations (grams of active element per milliliter of solution) of seven radiodense elements, including iodine, barium, gadolinium, tantalum, ytterbium, gold, and bismuth, were formulated as compounds in aqueous solutions. The compounds were chosen such that the active element dominated the x-ray attenuation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 38 publications
4
73
0
Order By: Relevance
“…23,32 Other high-Z elements with potential as possible CT contrast agents include gold, 33,34 ytterbium, 35 and gadolinium. 36 In the interest of simplicity, these elements were not considered in the current study; but based on our consistent findings for the high-Z elements we tested and the increased image contrast compared to iodine at higher energies for other high-Z elements, 19 one would expect that they, too, would exhibit the characteristic of contrast retention at high-keV levels compared to iodine in VMS images at higher energy levels.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…23,32 Other high-Z elements with potential as possible CT contrast agents include gold, 33,34 ytterbium, 35 and gadolinium. 36 In the interest of simplicity, these elements were not considered in the current study; but based on our consistent findings for the high-Z elements we tested and the increased image contrast compared to iodine at higher energies for other high-Z elements, 19 one would expect that they, too, would exhibit the characteristic of contrast retention at high-keV levels compared to iodine in VMS images at higher energy levels.…”
Section: Discussionmentioning
confidence: 83%
“…The main aim of this study was to compare the contrast profiles of the different elements, and as such, a detailed analysis of the composition and concentration was not a priority and has been performed rigorously elsewhere. 19 Fourth, the semisolid nature of the fat encasements did not allow for perfect repeatability between different setups, so the precision of those datasets is likely to be lower than for the initial 203-mm diameter phantom configuration. Fifth, a control phantom without artifact-producing metal implants was not imaged.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 However, these results were obtained using large, dense phantoms that represent the abdomen of an overweight-to-obese adult. The effect of these phantoms is to “harden” the X-ray spectrum, increasing the mean energy of the spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that the specific design of the zwitterionic ligand can affect the osmolality, viscosity, and renal clearance of the nanoparticles; we hypothesized that a design could be found that allows the nanoparticle to satisfy all physicochemical and biological safety requirements. Furthermore, a recent report 16 suggests that tantalum is the most promising candidate among the chemical elements evaluated for use in general-purpose CT contrast agents in terms of toxicity, cost, and availability. In addition, other work 17 predicts up to 65% improvement in CT image contrast for large-to-obese patients when tantalum-based rather than iodinated contrast agents are given at equal mass concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation